Age-Specific Helicobacter pylori Seropositivity Rates of Children in an Impoverished Urban Area of Northeast Brazil - Mitchell, Anastasia (American Society for Microbiology, 2003)
We determined age-specific Helicobacter pylori seropositivity rates of 166 children and 39 mothers in an urban shantytown in northeast Brazil. Seropositivity rates increased from 23.1% at 0 to 11 months of age to only 39.3% by 96 to 131 months of age and were 82.1% at maturity. We observed no correlation between the seropositivity of the mothers and the seropositivity of their children.